Whole transcriptome analysis of canine pheochromocytoma and paraganglioma - van den Berg, Marit F.; Kooistra, Hans S.; Grinwis, Guy C. M.; Nicoli, Stefano; Golinelli, Stefania; Stammeleer, Lisa; van Wolferen, Monique E.; Timmermans-Sprang, Elpetra P. M.; Zandvliet, Maurice M. J. M.; van Steenbeek, Frank G.; Galac, Sara (Frontiers in Veterinary Science, 2023)
Pheochromocytomas and paragangliomas (PPGLs) are neuroendocrine tumors arising from the chromaffin cells in the adrenal medulla and extra-adrenal paraganglia, respectively. Local invasion, concurrent disorders, and metastases prevent surgical removal, which is the most effective treatment to date. Given the current lack of effective medical treatment, there is a need for novel therapeutic strategies. To identify druggable pathways driving PPGL development, we performed RNA sequencing on PPGLs (n = 19) and normal adrenal medullas (NAMs; n = 10) of dogs. Principal component analysis (PCA) revealed that PPGLs clearly clustered apart from NAMs. In total, 4,218 genes were differentially expressed between PPGLs and NAMs. Of these, 232 had a log2 fold change of >3 or < −3, of which 149 were upregulated in PPGLs, and 83 were downregulated. Compared with NAMs, PPGLs had increased expression of genes related to the cell cycle, tumor development, progression and metastasis, hypoxia and angiogenesis, and the Wnt signaling pathway, and decreased expression of genes related to adrenal steroidogenesis. Our data revealed several overexpressed genes that could provide targets for novel therapeutics, such as Ret Proto-Oncogene (RET), Dopamine Receptor D2 (DRD2), and Secreted Frizzled Related Protein 2 (SFRP2). Based on the PCA, PPGLs were classified into 2 groups, of which group 1 had significantly higher Ki67 scores (p = 0.035) and shorter survival times (p = 0.04) than group 2. Increased expression of 1 of the differentially expressed genes between group 1 and 2, pleiotrophin (PTN), appeared to correlate with a more aggressive tumor phenotype. This study has shed light on the transcriptomic profile of canine PPGL, yielding new insights into the pathogenesis of these tumors in dogs, and revealed potential novel targets for therapy. In addition, we identified 2 transcriptionally distinct groups of PPGLs that had significantly different survival times.